Vigilancia tecnológica para estudiantes universitarios. El caso de la universidad nacional de Colombia, sede manizales (2016)
This article presents the results of a research that aims to establish the perception of technological surveillance of undergraduate students at the Manizales Campus of the National University of Colombia. Technological surveillance, viewed as the permanent gathering of information about science and technology to convert it into knowledge, is not being well utilized by students. For the study, methods of observation, analysis and synthesis and a type of exploratory and correlational descriptive approach were used. The results show that the university is making significant efforts by the acquisition of technological tools and investing resources in mass media diffusion. However, students do not perceive these advances in an appropriate way and are not applying the available systems. For instance, the students are not massively using one of the most popular resources such as the mobile phones to make adequate technological surveillance. This study contributes to the academic community to define a baseline to future actions to enhance the use of technological surveillance tools in learning processes.